DEVELOPMENT AND STUDY OF THE OPERATION OF THE MODULE FOR DETERMINING THE ORIENTATION OF THE MANIPULATOR JOINT - Nevlyudov, Igor; Novoselov, Sergiy; Sychova, Oksana (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2022)
In the field of mechatronic systems, manipulators are often used for automated assembly of products, welding, painting parts and more. An important task is to optimize the travel time along a given trajectory of the manipulator. To solve this problem, it is necessary not only to accurately estimate the speed of the manipulator nodes, but also to provide a linear characteristic of the assessment of the position of the mechanism in a wide range of speeds. The matter of the article are methods for determining the orientation of the joint of the manipulator. The goal of the work is to develop a module for determining the orientation of the joint of the manipulator and study its operation in order to determine the suitability subject of the structure for practical use. The following tasks are solved in the article: to investigate the principles of determining the orientation of the joints of industrial robots; choose the design of the orientation determination module; develop an algorithm for determining the position of the joint at any time; perform experimental studies of the position determination module in order to confirm the suitability of the structure for practical use. The following methods used are: experimental research was conducted on a real object - a model of the manipulator joint, created using methods and tools of 3D prototyping; to determine the position of the joint of the manipulator used methods of processing signals received from sensors; processing of experimental results and calculation of values of errors of positioning of a joint of the manipulator is based on methods of the statistical analysis of random sizes. The following results were obtained: the principles of determining the orientation of the joints of industrial robots were studied; the design is developed and the module of definition of orientation of a joint of the manipulator is created; developed an algorithm for determining the position of the joint at any time; the suitability of the design for practical use has been experimentally confirmed. Conclusions: in this paper, two variants of the sensor design are proposed to determine the absolute angle of rotation of the manipulator joint: resistive and magnetic. The proposed design of the resistive sensor was non-technological and much larger than the design of the magnetic sensor. The data obtained in the process of conducting experimental studies of the proposed method of measuring the angle of rotation of the mechanical gearbox of the manipulator joint indicate a fairly accurate determination of the angle using a magnetic sensor. The calculated measurement error was less than 1.4 degrees. The results of the experiment also showed that in addition to the radial direction of movement of the gearbox of the manipulator joint there is a significant displacement along the working plane, and in some cases, such displacements are chaotic. This is due to some defects and imperfections of the surface of the manufactured parts of the joint model used in research.